Excited state electronic structure, excitation energy transfer, and charge separation dynamics in various natural and artificial photosynthetic systems containing zinc and magnesium chlorins - Neupane, Bhanu (Kansas State University, 2011)
This dissertation reports the low temperature frequency domain spectroscopic study of three different natural pigment protein complexes and one artificial antenna system. The main focus of this work is to better understand electronic structure, excitation energy transfer (EET), and electron transfer (ET) dynamics in these systems that could have impact on achieving higher efficiency in future artificial solar cells. In the first part of this dissertation, electronic structure and EET pathways in isolated intact CP43 prime protein complex, which is isolated from Cyanobacterium synechocystis PCC 6803 grown under iron stressed conditions, are investigated using low-temperature absorption, fluorescence, fluorescence excitation, and hole-burning (HB) spectroscopies. This work suggests that, in analogy to the CP43 complex of PSII core, CP43 prime possesses two quasi-degenerate low energy states, A prime and B prime. The various low-temperature optical spectra are fitted considering an uncorrelated EET model. This work suggests that for optimal energy transfer from CP43 prime to PSI, the A prime and B prime state chlorophylls belonging to each CP43 prime should face towards the PSI core. The second part of dissertation reports the photochemical HB study on novel Zinc bacterial reaction center (Zn-RC) from Rhodobacter sphaeroides and its β-mutant (Zn-β-RC). This study shows that ET in the two samples is similar; however, the quantum efficiency of charge separation in the mutant decreases by 60 %. This finding suggests that the coordination state of the HA site zinc bacteriochlorophyll does not tune the active branch ET. Simultaneous fits of various optical spectra using experimentally determined inhomogeneity provides more reliable electron phonon coupling parameters for the P870 state of both RC samples. In the last part of this dissertation, EET in a novel artificial antenna system (ethynyl linked chlorophyll trefoil, ChlT1) is investigated. EET time in ChlT1 is ~2 ps. ChlT1 in MTHF/ethanol glass forms four different types of aggregates, A1-A4. The EET time in A1 and A2 type aggregates slows down only by a factor of 5 and 7, respectively. This study suggests that ChlT1 and its aggregates can be used as efficient antenna systems in designing organic solar cells.
Keywords: Photosynthesis; Spectral hole burning; Chemistry (0485)